2021
DOI: 10.3390/ijerph18052689
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Characteristics in the World Trade Center Environmental Health Center

Abstract: The destruction of the World Trade Center (WTC) towers on 11 September 2001 resulted in acute and chronic dust and fume exposures to community members, including local workers and residents, with well-described aerodigestive adverse health effects. This study aimed to characterize lung cancer in the WTC Environmental Health Center (WTC EHC) focusing on gender and smoking history. WTC EHC patients undergo an initial evaluation that includes WTC exposure information, demographics, and tobacco use. Detailed cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The World Trade Center Environmental Health Center conducted a study among people who were exposed and possibly inhaled dust and fumes from the destruction of the World Trade Center towers in 2001. The results showed that lung adenocarcinoma was more common in never-smokers compared to ever-smokers (72% vs. 65%) and more common in women compared to men (70% vs. 65%) (29). One study in China showed that though the proportion of lung adenocarcinoma increased in smokers and non-smokers, lung adenocarcinoma was more common in non-smokers (30).…”
Section: Discussionmentioning
confidence: 99%
“…The World Trade Center Environmental Health Center conducted a study among people who were exposed and possibly inhaled dust and fumes from the destruction of the World Trade Center towers in 2001. The results showed that lung adenocarcinoma was more common in never-smokers compared to ever-smokers (72% vs. 65%) and more common in women compared to men (70% vs. 65%) (29). One study in China showed that though the proportion of lung adenocarcinoma increased in smokers and non-smokers, lung adenocarcinoma was more common in non-smokers (30).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of lung cancers in the WTC EHC were previously described by our group, demonstrating that more than half of all lung cancers occurred in women, and of these, a high proportion were noted in never-smokers (48%) [27]. This is particularly important given the reported 15% incidence of lung cancer in women never-smokers in the U.S. [28].…”
Section: Discussionmentioning
confidence: 56%
“…Additionally, we identified biomarkers that were associated with WTC exposure. Our group and others have previous established association of WTC exposures with LRS, cancer, mental health disorders, neuropathic symptoms, and cognitive declines in WTC survivors [35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 65%